1998
DOI: 10.1046/j.1365-2168.1998.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of acute small bowel obstruction

Abstract: Laparoscopy can be performed in a high percentage of patients requiring surgery for acute small bowel obstruction. Hospital stay was reduced but the risk of early unplanned reoperation was increased in patients managed laparoscopically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
63
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 4 publications
8
63
0
5
Order By: Relevance
“…Laparoscopically treated patients had a significantly shorter hospital stay than patients who underwent conversion, as reported also in other studies [2,6,19], leading to lower total hospital costs [2]. In our study, the difference in the length of hospital stay between converted and nonconverted cases was 6 days.…”
Section: Discussionsupporting
confidence: 71%
“…Laparoscopically treated patients had a significantly shorter hospital stay than patients who underwent conversion, as reported also in other studies [2,6,19], leading to lower total hospital costs [2]. In our study, the difference in the length of hospital stay between converted and nonconverted cases was 6 days.…”
Section: Discussionsupporting
confidence: 71%
“…Prior abdominal surgery, which is often performed through a midline laparotomy, leads to adhesions of the small and large bowel to the anterior abdominal wall, and blind insertion may cause inadvertent perforation of the adjacent hollow viscus organs. Dilated bowel loops are a common problem in cases of emergency laparoscopy and cases of adhesion-and cancer-related (peritoneal carcinomatosis) bowel obstruction, so open access is probably safer than blind puncture of the abdominal cavity in these circumstances [1]. As far as we could tell, neither the type, size, or shape of the trocar contributed to an increased risk of perforating lesions.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, no perforation or recurrent obstruction was missed in this series. Unplanned reoperations are reported in 6-14 per cent of patients such as these 25,28 . Although intraoperative bowel perforation did not worsen the postoperative course, the incidence during laparoscopic treatment was nearly twice that of conventional open operation, and perforation was significantly more common in patients with two or more previous laparotomies.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, patients in whom laparoscopic treatment was intended had fewer postoperative complications, quicker recovery of bowel movements and a shorter hospital stay than conventionally treated patients. Bailey et al 28 have also shown a shorter hospital stay after laparoscopic compared with open management of acute SBO. An advantage with regard to bowel movements has been described previously only for laparoscopically treated patients compared with those whose operations for acute SBO were converted 24 .…”
Section: Discussionmentioning
confidence: 95%